Nikt nie woła Józefa Hena – Polska? Czy jednak życie? W poszukiwaniu żydowskiego „ja” - Przymuszała, Beata (Załącznik Kulturoznawczy, 2022)
The article devoted to the autobiographical layer of Józef Hen’s book Nikt nie woła shows the relationships between its hero, Bożek, and the problem of Jewish identity. Looking for the sense of his own strength the protagonist uses film metaphors. Their use may be related to an anti-Semitic experience: young Hen felt betrayed by a boy who held such views. The confusion he experienced then can still be felt, provoking questions about who you are and who you are feeling.